2013
DOI: 10.1371/journal.pone.0055238
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Tomato Flower Pedicel Tissues Reveals Abscission Zone-Specific Modulation of Key Meristem Activity Genes

Abstract: Tomato flower abscises at the anatomically distinct abscission zone that separates the pedicel into basal and apical portions. During abscission, cell separation occurs only at the abscission zone indicating distinctive molecular regulation in its cells. We conducted a transcriptome analysis of tomato pedicel tissues during ethylene promoted abscission. We found that the abscission zone was the most active site with the largest set of differentially expressed genes when compared with basal and apical portions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 60 publications
7
67
0
Order By: Relevance
“…Abebie et al (2008) reported that the floret abscission in cestrum cut flower was associated with the expression level of AUX/IAA genes, which was consistent with the results reported by Meir et al (2010). Likewise, there are also several reports suggesting GH3 genes are involved in fruitlet or flower abscission (Kuang et al 2012;Wang et al 2013). The above-mentioned results suggested that the roles of GH3s, ARFs and AUX/IAAs in fruitlet abscission may considerably vary among plant species.…”
Section: Introductionsupporting
confidence: 77%
“…Abebie et al (2008) reported that the floret abscission in cestrum cut flower was associated with the expression level of AUX/IAA genes, which was consistent with the results reported by Meir et al (2010). Likewise, there are also several reports suggesting GH3 genes are involved in fruitlet or flower abscission (Kuang et al 2012;Wang et al 2013). The above-mentioned results suggested that the roles of GH3s, ARFs and AUX/IAAs in fruitlet abscission may considerably vary among plant species.…”
Section: Introductionsupporting
confidence: 77%
“…This set of cellular characteristics is reminiscent of meristematic tissues. Several genes involved in SAM maintenance and the initiation of axillary meristems are expressed in the AZ (Shi et al, 2011;Nakano et al, 2013;Wang et al, 2013). Therefore, it has been proposed that AZ cells have a meristematic identity.…”
Section: Osh15-qsh1 Dimer Functions For Az Developmentmentioning
confidence: 99%
“…The process includes four major steps: development of the AZ tissue, acquisition of competence to respond to abscission signals, activation of abscission following perception of abscission signals, and differentiation of a protective layer on the proximal side of the AZ (Patterson 2001). Extensively transcriptome analyses have been performed to investigate the gene expression changes during organs shedding among different plant species and in different AZs of leaves, fruits and flowers Agustí et al 2008;Cai and Lashbrook 2008;Meir et al 2010;Botton et al 2011;Nakano et al 2012Nakano et al , 2013Wang et al 2013). These studies revealed that the abscission-related genes are mostly involved in ethylene and auxin biosynthesis and signal transduction, cell wall modification, and various stress responses Agustí et al 2008;Cai and Lashbrook 2008;Meir et al 2010;Botton et al 2011;Nakano et al 2012Nakano et al , 2013Wang et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Extensively transcriptome analyses have been performed to investigate the gene expression changes during organs shedding among different plant species and in different AZs of leaves, fruits and flowers Agustí et al 2008;Cai and Lashbrook 2008;Meir et al 2010;Botton et al 2011;Nakano et al 2012Nakano et al , 2013Wang et al 2013). These studies revealed that the abscission-related genes are mostly involved in ethylene and auxin biosynthesis and signal transduction, cell wall modification, and various stress responses Agustí et al 2008;Cai and Lashbrook 2008;Meir et al 2010;Botton et al 2011;Nakano et al 2012Nakano et al , 2013Wang et al 2013). Wang et al (2013) conducted a transcriptome analysis of tomato pedicel tissues during ethylene promoted abscission, and found that the abscission zone was the most active site with the largest set of differentially expressed genes when compared with basal and apical portions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation